Bionomics of black flies (Diptera: Simuliidae) in Costa Rica. V. Description of Neomesomermis travisi sp. n. (Nematoda: Mermithidae) - Vargas V., Mario (1980)
Neomesomermis travisi sp. n., a mermithid parasite of larvae of Simulium panamense and Simulium melallicum is described from Costa Rica, Central America. This species, the first mermithid described from the Neotropical Region, is very close to Neomesomermis flumenalis Welch, 1962 but can be differentiated by the distinct serrations on the tips of the spicules; those of N. flumenalis being distinctly smooth, and the tail of the female adults more bluntly rounded than in N. flumenalis. Narrow chords, small amphids, bulbous vagina, large eggs in two rows, and the genital structures of the male of N. travisi also differ from those of other, closely allied, Holoarctic species of Neomesomermis. Detailed measurements of taxonomically important structures of different life stages are presented and illustrated.